Roosting ecology and morphometric analysis of Pteropus medius (Indian flying fox) in Lower Dir, district, Pakistan - Khan,W. (2021)
Abstract The present study was conducted to explore morphometric variations of Pteropus medius (the Indian flying fox) and the roosting trees in Lower Dir, Pakistan. The bats were captured from Morus alba, Morus nigra, Brousonetia papyrifera, Pinus raxburghii, Hevea brasiliensis, Platanus orientalis, Populous nigra, Melia azedarach, Eucalyptus camaldulensis and Grevillea robusta through sling shot and mess net methods. A total of 12 bats were studied for the differential morphological features based on age and sex. Male bats were recorded higher in weight than females. The variations were found in body mass (821.1±34.65gm), circumference of body with wings (25.43±0.39cm), wingspan (112.58±1.90cm), Body length (20.73±0.68cm), Snout length (3.42±0.04cm), Eye length (1.45±0.033cm), Length of ear (3.56±0.05cm), Width of ear (2.46±0.04cm), Length b/w ear (5.51±0.11cm), Circumference of neck (12.23±0.24cm), Circumference of body without wings (18.68±0.31cm), Arm wing length (23.2±1.03cm), Length of thumb (5.43±0.1cm), Length of nail (1.89±0.05cm), Hand wing length (29.1±0.51cm), Maximum width of wing (21.03±0.68cm), Length b/w tip of wing to 5th digit (29.39±0.30cm), Length b/w 5th digit to foot (22.97±1.09cm), Length b/w feet (18.31±0.74cm) and Length of foot claw (4.23±0.05cm). This study was designed for analysis of external morphological variations for P. medius (the Indian flying fox) that may help in identification of these bats and their roosting sites.